IL-10 Serum Concentration was Observed Higher in Threatened Preterm Labor - Nurul Afriana (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To determine the serum concentration of Th-1 and Th-2 cytokine in threatened preterm labor compared to that in normal pregnancy. Method: The design was analytical cross-sectional, comparing the serum levels of TNF-Î±, IL-2, IL-10, TNF-Î± to IL-10 ratio and IL-2 to IL-10 ratio between 29 subjects with threatened preterm labor and 29 normal pregnant women. The cytokine concentration was measured with ELISA. T test and Mann-Whitney U test was used for statistical analysis. Results: The mean concentration of TNF-Î± and IL-2 in both groups did not reveal any difference (p = 0.188 and p = 0.493). Median of IL-10 serum concentration in the threatened preterm labor (PTL) group was observed higher than that observed in the normal pregnancy group (p = 0.001). Compared to normal pregnancy group, the TNF-Î± to IL-10 ratio in the PTL group was observed lower (p = 0.009). Both groups did not show any difference in the IL-2 to IL-10 ratio (p = 0.057). Conclusion: The IL-10 serum concentration was increased in threatened preterm labor. There was no difference observed in the Th-1 to Th-2 cytokines serum ratio in threatened preterm labor as compared to normal pregnancy. [Indones J Obstet Gynecol 2010; 34-4: 191-4] Keywords: IL-10, preterm labor, Th-1 and Th-2 cytokines